2006
DOI: 10.1051/forest:2005091
|View full text |Cite
|
Sign up to set email alerts
|

Can understory vegetation accurately predict site index? A comparative study using floristic and abiotic indices in sessile oak (Quercus petraea Liebl.) stands in northern France

Abstract: -We investigated the relevance of understory vegetation in indicating site productivity as expressed by sessile oak (Quercus petraea Matt. Liebl.) site index over a large territory. The relationships between site index and (1) understory vegetation or (2) soil, topography and climate were studied using data from 99 even-aged high-forest stands located in northern France. Multiple regressions using floristic indices as predictors explained the same part of variance in site index as regressions using climate, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 47 publications
0
22
0
1
Order By: Relevance
“…According to the suggestions of some authors [21,28,40] Tab. 1 Characteristics of the study area of the Sopot river valley ( [34,35] and Czarnecka unpblished data).…”
Section: Discussionmentioning
confidence: 99%
“…According to the suggestions of some authors [21,28,40] Tab. 1 Characteristics of the study area of the Sopot river valley ( [34,35] and Czarnecka unpblished data).…”
Section: Discussionmentioning
confidence: 99%
“…Climatic indices and soil water capacity were used to calculate an annual soil water deficit (SWD) based on a simplified soil water balance model. Vegetation was measured inside 20 m  20 m quadrats and used to calculate floristic indices that also reflected ecological gradients as analysed by Bergès et al (2006). Three types of ecological variables were used: (1) climate, topography, chemical and physical soil characteristics, (2) mean Ellenberg indicator values for light (mL), temperature (mT), continentality (mK), soil moisture (mF), soil reaction (mR) and soil nitrogen (mN) (Ellenberg et al, 1992), and (3) the first three principal coordinates of a correspondence analysis performed on the floristic matrix (composed of 99 plots and 163 species).…”
Section: Ecological Data Collectionmentioning
confidence: 99%
“…However, using the ground vegetation as an indicator of site quality has several limitations, since the vegetation composition is affected by many factors. In forest ecosystems, such factors are primarily tree layer, especially its structure and tree species composition (Križová, Ujházy 1998;Ewald 2000;Fischer et al 2002;Bošeľa et al 2007) and disturbance history (Bergès et al 2006). On the other hand, Bergès et al (2006) observed that understorey vegetation ex- plained the same portion of variance in sessile oak site index as soil, climate and topography.…”
Section: Discussionmentioning
confidence: 99%